Update on Malacology - Ray, Sajal; Mukherjee, Soumalya (IntechOpen, 2022)
Update on Malacology is a compilation of high-impact research articles on the frontier areas of molluscan biology, physiology, aquaculture, and paleoecology. Topics covered include effects of dietary intake of shellfish in humans, beneficial effects of herbal compounds on the cognitive ability of molluscs, seasonal variation of molluscs acting as intermediate hosts of human parasites, current understanding of freshwater pearl culture, and the role of environmental parameters on the infectivity of freshwater snails and their paleoecological aspects. This book is an enriched edition of current trends of malacological research and is a useful resource for students, teachers, and researchers working in basic and applied malacology.